IgE Cross-Reactivity of Cashew Nut Allergens - Bastiaan-Net, Shanna; Reitsma, Marit; Cordewener, Jan H.G.; van der Valk, Johanna P.M.; America, Twan A.H.P.; Dubois, Anthony E.J.; Gerth van Wijk, Roy; Savelkoul, Huub F.J.; de Jong, Nicolette W.; Wichers, Harry J. (International archives of allergy and immunology, 2019)
Background: Allergic sensitisation towards cashew nut often happens without a clear history of eating cashew nut. IgE cross-reactivity between cashew and pistachio nut is well described; however, the ability of cashew nut-specific IgE to cross-react to common tree nut species and other Anacardiaceae, like mango, pink peppercorn, or sumac is largely unknown. Objectives: Cashew nut allergic individuals may cross-react to foods that are phylogenetically related to cashew. We aimed to determine IgE cross-sensitisation and cross-reactivity profiles in cashew nut-sensitised subjects, towards botanically related proteins of other Anacardiaceae family members and related tree nut species. Method: Sera from children with a suspected cashew nut allergy (n = 56) were assessed for IgE sensitisation to common tree nuts, mango, pink peppercorn, and sumac using dot blot technique. Allergen cross-reactivity patterns between Anacardiaceae species were subsequently examined by SDS-PAGE and immunoblot inhibition, and IgE-reactive allergens were identified by LC-MS/MS. Results: From the 56 subjects analysed, 36 were positive on dot blot for cashew nut (63%). Of these, 50% were mono-sensitised to cashew nuts, 19% were co-sensitised to Anacardiaceae species, and 31% were co-sensitised to tree nuts. Subjects co-sensitised to Anacardiaceae species displayed a different allergen recognition pattern than subjects sensitised to common tree nuts. In pink peppercorn, putative albumin- and legumin-type seed storage proteins were found to cross-react with serum of cashew nut-sensitised subjects in vitro. In addition, a putative luminal binding protein was identified, which, among others, may be involved in cross-reactivity between several Anacardiaceae species. Conclusions: Results demonstrate the in vitro presence of IgE cross-sensitisation in children towards multiple Anacardiaceae species. In this study, putative novel allergens were identified in cashew, pistachio, and pink peppercorn, which may pose factors that underlie the observed cross-sensitivity to these species. The clinical relevance of this widespread cross-sensitisation is unknown.